Tantangan Kepemimpinan Pendidikan Islam di Era Globalisasi 5.0 - Dwika Putra; Edi Supriyatno; Halimah Halimah; Al Mahfuz (Arbain Publishing, 2025)
The Era of Globalization 5.0 presents complex challenges for Islamic educational leadership, where the integration of religious values must align with the demands of modernity and technological advancement. This article analyzes the dynamics of globalization that influence the identity, quality, and relevance of Islamic education through a multidimensional approach encompassing social, cultural, economic, and technological perspectives. Data from international institutions such as UNESCO, UNICEF, the World Bank, and the Pew Research Center indicate that the digitalization of education, inequality of access, and the penetration of global culture may weaken traditional values while simultaneously creating opportunities for curriculum innovation and educational management transformation. Leaders in Islamic education are required not only to serve as administrators but also as agents of change who can integrate digital technology, develop human resource quality, and strengthen students’ character based on the Qur’an and Sunnah. This article emphasizes that Islamic educational leadership in the era of globalization demands strategic vision, cross-sector collaboration, and continuous innovation to nurture a generation of Muslims who are strong in character, globally competitive, and firmly rooted in authentic Islamic values.